2014
DOI: 10.1007/s12262-014-1068-8
|View full text |Cite
|
Sign up to set email alerts
|

Different Sutures in the Surgical Treatment of Acute Closed Achilles Tendon Rupture

Abstract: The aim was to compare the postoperative efficacy of the PDS II and Ethibond W4843 sutures in fresh, closed Achilles tendon rupture. With methods of random grouping (level of evidence II b), a total of 128 patients with fresh Achilles tendon rupture were operated on with PDS II or Ethibond W4843 suture. Postoperative objective examination and the American Orthopaedic Foot & Ankle Society (AOFAS) scoring system were used for the evaluation. Group A underwent 12-39 months of follow-up, for an average of 22 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Mechanistic research would also contribute to our understanding of Achilles tendon healing. 15,18,21,53…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic research would also contribute to our understanding of Achilles tendon healing. 15,18,21,53…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the AOFAS score and pain score, the Ethibond suture performed better. 19 For six-strand repair, we used total three sutures with three knots (i.e. the most proximal suture will pass through both the most proximal and the most distal hole as well to create only one knot in a pair) instead of six sutures with six knots (i.e.…”
Section: Authors' Suggestion With This Devicementioning
confidence: 99%
“…Rates of foreign body reaction in the included studies showed no heterogeneity ( P = .62; I 2 = 0%); that being the case, fixed effects model was used. Events assessed in Ji et al 6 were adhesion rates resulting from inflammation and the coagulation process. Results showed that patients in the nonabsorbable sutures group had no significantly different foreign body reaction than patients in the absorbable suture group (risk difference −0.02, 95% CI −0.11 to 0.07; P = .69) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias from each study included will be assessed using the Cochrane Risk of Bias Tool 6 for randomized study (RoB 2) and Risk of Bias in Non-Randomized Studies of Interventions (ROBINS-I) 10 for nonrandomized study by 2 authors (I.O., A.F.C.) independently and disagreement were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%